A Comparative Study of Off-Task Behavior in the Classroom Among Senior and Vocational High School Students in Salatiga: Analysis of Aspect and Causal Factor - Glorya Cipta Husada Nusantara; Dewita Karema Sarajar (G-Couns: Jurnal Bimbingan dan Konseling, 2026)
Not all students remain focused during classroom learning. Some engage in other activities that divert their attention from the learning process. This behavior is known as off-task behavior. This study examines six aspects of off-task behavior in classrooms: inattention, out of seat, noncompletion of task, talking without permission, unmotivated to learn, and unprepared for class, among high school and vocational school students in Salatiga. This research employs a quantitative comparative method with an Independent Sample t-test for statistical analysis. The participants are 500 students, including 250 high school students and 250 vocational school students, selected through purposive sampling. Results indicate no significant difference in off-task behavior between high school and vocational school students (p = 0.451). Both high school and vocational school students predominantly fall into the moderate category. This study provides insights into differences in behavioral tendencies and aspects of off-task behavior in the classroom. Keywords: off-task behavior, classroom, student, senior high school, vocational high school, secondary education